Analisis Observasional dan Perbaikan Sistem Penerangan pada Mobil Mazda MR90 - Dadang Rustandi; Kasum Kasum; Nurhidayati Nurhidayati; Kasman Kasman; Matius Feliks Jordan (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
The lighting system of the Mazda MR90 is designed to support driving safety by making the vehicle visible to other road users and enabling the driver to observe surrounding road conditions. This study aims to analyze the working principle, identify faults, and carry out repairs on the main components of the Mazda MR90 lighting system. The study used a descriptive method with an observational approach through visual inspection, functional testing, and checking electrical current paths using a test pen at the Automotive Laboratory of Akademi Teknologi Bogor. The inspection covered the headlamps, rear lamps, turn signals, hazard lamps, reverse lamps, fuses, flasher, switches, relays, sockets, and wiring. The inspection found that the turn signals and hazard lamps did not blink, the reverse lamp did not light, and several wiring paths were damaged or disconnected. Repairs included replacing the flasher and reverse-lamp bulb and repairing and reconnecting damaged wiring. Post-repair testing showed that all repaired components returned to normal operation. These findings indicate that systematic diagnosis can identify faulty components and support targeted repair of a conventional vehicle lighting system.